2022
DOI: 10.1021/acs.jpcc.2c00807
|View full text |Cite
|
Sign up to set email alerts
|

Study of Phase Transformation Processes Occurring in the Nanocrystalline Iron/Ammonia/Hydrogen System by the Magnetic Permeability Measurement Method

Abstract: Phase transformations over a nanocrystalline iron catalyst in the nitriding process were carried out at 350 °C and under atmospheric pressure. The process was conducted under conditions of changing nitriding potential both during the nitriding and reduction of iron nitrides. These processes were monitored by measuring the magnetic permeability and changes of mass and reaction gas composition. Four stages of nitriding were observed and ascribed to the following general schematic reactions:The measurements of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…The composition of the obtained iron nitrides depends on t nitriding temperature and the nitrogen potential [19,20]. Arabczyk et al [21] annealed nanocrystalline iron catalyst in an NH3/H2 atmosphere at 350 °C with a varying nitrog potential value during both nitriding and iron nitride reduction. During the process, t authors recorded a change in the magnetic permeability of the created nitride phase Tests showed that the magnetic permeability of γ′-Fe4N was 1.280 times higher than th of an iron catalyst, while that of ε-FexN was more than 3 times lower.…”
Section: Materials and Parameters Of Nitriding And Annealingmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the obtained iron nitrides depends on t nitriding temperature and the nitrogen potential [19,20]. Arabczyk et al [21] annealed nanocrystalline iron catalyst in an NH3/H2 atmosphere at 350 °C with a varying nitrog potential value during both nitriding and iron nitride reduction. During the process, t authors recorded a change in the magnetic permeability of the created nitride phase Tests showed that the magnetic permeability of γ′-Fe4N was 1.280 times higher than th of an iron catalyst, while that of ε-FexN was more than 3 times lower.…”
Section: Materials and Parameters Of Nitriding And Annealingmentioning
confidence: 99%
“…The composition of the obtained iron nitrides depends on the temperature and the nitrogen potential [19,20]. Arabczyk et al [21] annealed a stalline iron catalyst in an NH3/H2 atmosphere at 350 °C with a varying nitrogen l value during both nitriding and iron nitride reduction. During the process, the recorded a change in the magnetic permeability of the created nitride phases.…”
Section: Phase Transformations Of Iron Nitridesmentioning
confidence: 99%
“…The first such research was conducted by Lehrer, who nitrated iron powder in a stream of a flowing mixture of ammonia and hydrogen [11]. Moszy ńska et al and Arabczyk et al demonstrated that during nitriding, phase transformations in the iron nitride layer can be induced by changing the value of the nitrogen potential [12,13].…”
Section: Introductionmentioning
confidence: 99%